Struktur Komunitas Cacing Tanah (Kelas Oligochaeta) di Kawasan Hutan Desa Mega Timur Kecamatan Sungai Ambawang - Ari Hepi Yanti, Firmansyah, Tri Rima Setyawati, (Jurnal Protobiont, 2017)
Community structure can be reviewed from its species composition, species density, species evenness, species diversity, species dominance, and species biomass in an ecosystem. Earthworms have an important role in decomposition process of organic matters. The existence of earthworms can be considered as a bioindicator of soil productivity. A research about community structure of earthworms in Mega Timur Village forest area had been conducted in August 2016. This research aims to know the community structure of earthworms (class Oligochaeta) that are found in Mega Timur Village forest area as well as the condition of their habitat. Plot sampling was taken randomly with 5 plots whose size is 5x5m2 on every location. The sampling method used was quadrate method with size 30x30cm2, taking 5 spots on each location and hand-sorting method. Earthworms found in the site included three genera: Pheretima, Perionyx, and Pontoscolex. The highest composition of earthworms was found in Station I and III with two genera each, and the lowest composition was found in Station II with only one genus. Genus Pontoscolex had the highest density index, while genus Pheretima had the lowest index. The highest diversity index was observed in Station III (H’=0,64), while the lowest diversity index was on Station I (H’=0).